PENGARUH PROMOSI KESEHATAN TENTANG RISIKO CEDERA KEPALA TERHADAP SIKAP REMAJA DALAM MENGGUNAKAN HELM - Rahman, Waldi; Martin, Weddy; Ramadhan, Rahmi; Pelani, Helman; Eliza, Eliza (Ensiklopedia Education Review, 2023)
Traffic accidents kill nearly 1.2 million people worldwide and injure around 6 million people every year. The highest number of traffic accident victims based on age is in the productive age group, especially in the 16-30 year age range. One of the effective efforts to reduce the number of teenage deaths caused by traffic accidents is by using motorbike helmets. There is a lack of information and publicity efforts that it is very important to use a motorbike helmet, especially because head injuries are the quickest cause of death. The aim of this research is to determine the effect of health promotion regarding the risk of head injury on the knowledge and attitudes of adolescents in using motorbike helmets at SMAN 1 Enam Lingkung, Padang Pariaman Regency. The design of this research is a pre-experimental one group pre-post test design. The sample studied was 25 people selected using purposive sampling technique. It is known that the average attitude before the intervention was 31.64 and after the intervention 33.16. From the statistical results on attitudes, the t value was 3.42 and P value = 0.002 < α (0.05). It was concluded that there was an influence of health promotion regarding the risk of head injury on teenagers' attitudes towards using motorbike helmets at SMAN 1 Enam Lingkung, Padang Pariaman Regency. Thus, it is hoped that health services and schools will further increase promotive efforts in publicizing safe riding to students.Keywords: Health Promotion, Attitude, Head Injuries, Motorcycle Helmets